Drainage and Salinity Problems in the Mexican Irrigation Districts: An Overview 1962-2013 - Palacios Vélez, Óscar Luis; Pedraza Oropeza, Felipe J. A. (Tecnología y ciencias del agua, 2015)
A brief description of the natural conditions that led to the development of irrigation in Mexico is presented, and some of the main problems that irrigation faces in present day are addressed. An overview of the modernization of the irrigation techniques, which began in 1962, when the first offices of irrigation and drainage engineering were created, is presented. These offices were created to give a technical support to the rehabilitation works that started in several irrigation districts. The main activities carried out by these offices were related to the irrigation improvement, as well as to the monitoring of water table levels and soil salinity. The activities of the so-called "Plan de Mejoramiento Parcelarioâ€ (best known as "Plamepaâ€, or Plan for Irrigation Improvement at the farm level), which had to do with the improvement of the overall water management efficiency, as well as with the works needed to increase the main crop yields, are also described. The problems that arise during the elaboration of water table and soil salinity maps are also commented. These problems include the definition of the threshold soil salinity content to consider a soil "salineâ€; the definition of a proper soil salinity sampling intensity, and the method of spatial interpolation for mapping. This information is crucial when planning the reclamation of saline soils by means of leaching. In the final part the consequences of the irrigation districts transfer from the federal government to the water users, on the irrigation, drainage and salinity studies and practices are commented.